Novel functional roles for PERIANTHIA and SEUSS during floral organ identity specification, floral meristem termination, and gynoecial development - Wynn, April N.; Seaman, Andrew A.; Jones, Ashley L.; Franks, Robert G. (Frontiers in Plant Science, 2014)
The gynoecium is the female reproductive structure of angiosperm flowers. In Arabidopsis thaliana the gynoecium is composed of two carpels fused into a tube-like structure. As the gynoecial primordium arises from the floral meristem, a specialized meristematic structure, the carpel margin meristem (CMM), develops from portions of the medial gynoecial domain. The CMM is critical for reproductive competence because it gives rise to the ovules, the precursors of the seeds. Here we report a functional role for the transcription factor PERIANTHIA (PAN) in the development of the gynoecial medial domain and the formation of ovule primordia that is revealed in aintegumenta (ant) pan and seuss (seu) pan double mutants. Additionally, enhanced disruptions of gynoecial morphology suggest that gynoecial patterning processes are disrupted in the seu pan double mutant. Previously, PAN was identified as a regulator of perianth organ number and as a direct activator of AGAMOUS expression in floral whorl four. However, the seu pan double mutants display enhanced ectopic AG expression in developing sepals and the partial transformation of sepals to petals indicating a novel role for PAN in the repression of AG in floral whorl 1. These results indicate that PAN functions as an activator or repressor of AG expression in a whorl specific fashion. The seu pan double mutants also display enhanced floral indeterminacy, resulting in the formation of “fifth whorl” structures and disruption of WUS expression patterns revealing a novel role for SEU in floral meristem termination.